The Protection of Children's Rights in Marriage Dispensation Cases before Indonesian Religious Courts: Examining the Impacts and Challenges - Fatroyah Ars Himsyah; Abdul Malik; Ria Astina (Hukum Keluarga Islam IAIN LANGSA, 2026)
The amendment of the minimum marriage age through Law Number 16 of 2019 was intended to curb child marriage and strengthen the protection of children’s rights in Indonesia. In practice, however, this policy has been followed by a significant increase in petitions for marriage dispensation in Religious Courts. This situation reveals a contradiction between the normative aim of the regulation, which is oriented toward preventing early marriage, and judicial practice that still provides legal avenues for child marriage through the dispensation mechanism. This study aims to analyze the implementation of child rights protection in the adjudication of marriage dispensation cases and to assess the application of the best interests of the child principle in judicial reasoning. Employing a normative juridical method with statutory and conceptual approaches, supported by an examination of court practice, the research finds that the high approval rate of dispensations, the dominance of premarital pregnancy as a ground, and the limited use of psychological and social assessments tend to undermine the child-protection objectives embedded in the regulatory reform. Accordingly, this study underscores the urgency of applying multidisciplinary assessments in marriage dispensation proceedings to ensure that the best interests of the child are genuinely fulfilled.